2016
DOI: 10.1017/s0007114515005504
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Dietary Approaches to Stop Hypertension-style diet in relation to glioma: a case–control study

Abstract: Data on the association of adherence to the Dietary Approaches to Stop Hypertension (DASH)-style and glioma are scarce. We aimed to examine the association between adherence to the DASH-style diet and glioma in Iranian adults. In this study, 128 pathologically confirmed cases of glioma were recruited from hospitals and 256 age-and sex-matched controls were enrolled from other wards of the hospital. Dietary intakes were assessed using a 126-item validated FFQ. Adherence to the DASH-style diet was followed consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…42 However, previous studies have used FFQs to measure DASH and to predict outcomes based on DASH adherence. 37,43 Second, the DASH indices used in this study had scores that ranged from 0-9 and most participants scored lower than a 4. This limits our ability to detect differences in outcomes between different levels of DASH adherence.…”
Section: Discussionmentioning
confidence: 94%
“…42 However, previous studies have used FFQs to measure DASH and to predict outcomes based on DASH adherence. 37,43 Second, the DASH indices used in this study had scores that ranged from 0-9 and most participants scored lower than a 4. This limits our ability to detect differences in outcomes between different levels of DASH adherence.…”
Section: Discussionmentioning
confidence: 94%
“…In light of the fact that dietary components are consumed in the context of mixed meals with their probable additive or synergistic effects on each other 11 , assessment of the role of dietary patterns in the pathogenesis of health outcomes is a priority. In this regard, greater adherence to the low carbohydrate diet 12 , Dietary Approaches to Stop Hypertension (DASH)-style pattern 13 , and Mediterranean diet 14 were inversely associated with the odds of glioma. In contrast, a positive relationship was reported between dietary inflammatory index and risk of glioma in earlier studies 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that greater adherence to AHEI was associated with decreased odds of glioma. In our earlier study, adherence to DASH diet, known as a high-quality dietary pattern, was associated with 72 % lower risk of glioma (12) . Findings of previous studies on the association between AHEI and risk of other cancers were also in line with our findings.…”
Section: Discussionmentioning
confidence: 86%